3D printing Mg-CHA bone repair material loaded with DMOG and rhBMP-2 and preparation method of 3D printing Mg-CHA bone repair material

By loading DMOG and rhBMP-2 on Mg-CHA and 3D printing with PCL, the shortcomings of existing bone repair materials in bone regeneration are solved, and the sequential release of DMOG and rhBMP-2 is achieved, improving the osteogenic effect and safety of bone repair materials.

CN119548668APending Publication Date: 2025-03-04THE SECOND HOSPITAL AFFILIATED TO WENZHOU MEDICAL COLLEGE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311131236.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing bone repair materials have problems such as short half-life, expensive and potential side effects in promoting bone regeneration, and the application prospects of 3D printing technology in the field of bone repair have not been fully utilized.

Method used

Mg-CHA was obtained by modifying carbonated hydroxyapatite with magnesium ions, and loading DMOG and thiolated modified rhBMP-2 by physical adsorption and chemical adsorption, respectively, to form DMOG/rhBMP-2@Mg-CHA bone repair material, and 3D printing was performed using PCL as the substrate.

Benefits of technology

The sequential release of DMOG and rhBMP-2 is achieved, simulating the sequence release of provascular and osteogenic factors during natural bone repair, improving the osteogenic activity and safety of bone repair materials, and is suitable for the application of 3D printing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548668A_ABST
    Figure CN119548668A_ABST
Patent Text Reader

Abstract

The invention provides a 3D printing Mg-CHA bone repair material loaded with DMOG and rhBMP-2 and a preparation method of the 3D printing Mg-CHA bone repair material. Mg-CHA is obtained by modifying carbonated hydroxyapatite with magnesium ions, DMOG is adsorbed on the Mg-CHA, and Mg < 2 + > on the Mg-CHA is coordinated with the sulfhydrylated rhBMP-2; dMOG is in full contact with mesopores in the surface of Mg-CHA through physical adsorption and is massively modified on Mg-CHA, rhBMP-2 is subjected to sulfhydrylation modification and then is coordinated with Mg < 2 + > metal on the surface of Mg-CHA to form chemical adsorption, and due to the fact that chemical adsorption is firmer than physical adsorption, sequential release of DMOG and rhBMP can be achieved, so that osteogenesis is promoted through the synergistic effect, and the effect of promoting osteogenesis is achieved. The material has huge potential as a 3D printing bone repair material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 and a preparation method thereof. Background Art

[0002] Bone is a dynamic, innervated, and vascularized tissue with an intrinsic ability to regenerate after injury. Therefore, most fractures or bone injuries can be completely healed without much intervention. However, severe bone defects may not heal on their own. Defects of critical size may be the result of interbody fusion, bone tumor resection, infection, severe trauma, or even developmental malformations, which require surgical restoration of bone volume. The use of bone substitutes to treat these defects is becoming increasingly common, with more than 2 million bone transplants performed each year worldwide. Current methods of harvesting bone include autografts (the gold standard), allografts, and xenografts. Both autografts and allografts are limited by donor tissue availability and donor site morbidity, while allografts and xenografts are subject to cost and disease transmission issues. These issues have prompted the current research into new, cost-effective methods to address these deficiencies through tissue engineering approaches. By incorporating new biomaterials, bone grafts can be given improved physicochemical properties, morphological presentation, and even cell therapy capabilities. This novel strategy offers hope for the shortage of available tissue and improves the potential for bone tissue regeneration.

[0003] The successful implantation of current bone repair materials depends on: (1) the shape of the implant matches the recipient site; (2) there is sufficient porosity to promote new bone growth; (3) the mechanical properties are consistent with the surrounding natural bone; (4) the cytocompatibility and biocompatibility of the material; (5) the bone conductivity of the implant; and (6) the implant material induces osteogenesis. Current clinically relevant biomaterials for bone repair include bone blocks, bone chips, and bone cement. Bone blocks are pre-formed cubic structures that provide controllable porosity but require the surgeon to trim sections to match the patient's anatomy, resulting in longer surgical times. Bone chips are fine cortical cancellous bones with good porosity but limited mechanical strength and poor bone integration. Finally, bone cement is a plastic, quick-setting paste that can be customized to the patient's anatomy but typically has low porosity.

[0004] Current studies have shown that bone morphogenetic protein (BMP), transforming growth factor-β (TGF-β), platelet-derived growth factor (PDGF), insulin-like growth factor (IGF), etc. are osteoinductive factors that play an important role in bone regeneration. Vascular endothelial growth factor (VEGF) is the main factor that induces angiogenesis. In the normal bone healing process, the expression of VEGF reaches a peak in the early stage, while the expression of BMP-2 reaches a peak in the later stage. According to the synergistic and additive effects between growth factors, VEGF first effectively induces angiogenesis, and then BMP-2 promotes bone formation. Therefore, the continuous release of these cytokines effectively promotes bone regeneration. Studies have shown that the combined release of BMP-2 and VEGF can accelerate the process of osteogenesis, and the sequential release of VEGF and BMP-2 can produce more new bone compared with the release of single factors. Therefore, controlling the sequential release of VEGF and BMP-2 can improve osteogenic activity.

[0005] For example, the invention patent with application number 202310220531.0 discloses a dual-factor gradient sustained-release bone repair material and its preparation method: collagen is mixed with acetic acid solution and stirred to obtain a collagen solution; the collagen solution is mixed with a calcium-containing compound and stirred, and then pre-frozen and freeze-dried in sequence to obtain a freeze-dried porous mixture; the freeze-dried porous mixture is mixed with a cross-linking agent and cross-linked, and then washed and freeze-dried in sequence, and then immersed in a PBS solution containing bone growth factor BMP-2 to obtain an inner layer of bone repair material; the photocurable material solution is mixed with endothelial growth factor VEGF to obtain an outer layer of bone repair material mixed solution; and finally photocuring is performed. The bone repair material obtained by this method has a double-layer structure. The outer layer can be rapidly vascularized in the early stage and establish a blood supply connection with the body to meet the transportation of oxygen, nutrients and metabolites of cells that migrate into the scaffold. The inner layer can still continuously stimulate osteogenesis in the later stage, and finally form living autologous bone tissue. However, exogenous VEGF and BMP-2 proteins have a short half-life and are easily degraded in the body, which greatly reduces their synergistic effect on osteogenesis. In addition, BMP-2 protein is not only expensive, but also has potential side effects. Especially in spinal interbody fusion surgery, BMP-2 doses exceeding the physiological dose may cause uncontrollable osteogenesis in the defect area.

[0006] The application prospects of 3D printing technology have been recognized in the field of bone repair. 3D printing technology has unique advantages in micropore accuracy, personalization, pore regulation, spatial structure complexity, mechanical strength, etc. It can be combined with bone repair materials to achieve better osteogenesis. Therefore, the applicant hopes to invent a bone repair material that is suitable for 3D printing and can solve the above-mentioned technical problems. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 and a preparation method thereof. The technical solution adopted by the present invention is as follows: A method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2, wherein Mg-CHA is obtained by modifying carbonated hydroxyapatite with magnesium ions, and DMOG is adsorbed on the Mg-CHA, and the Mg on the Mg-CHA 2+ Coordinates with thiolated rhBMP-2.

[0008] Preferably, the specific method steps include: S1. Based on hydroxyapatite HA, HA is modified by replacing phosphate with phosphate and hydroxyl to form porous carbonated hydroxyapatite CHA, and Mg is modified on CHA to form Mg-CHA; S2. Mg-CHA was loaded with DMOG by physical adsorption, and Mg-CHA was loaded with thiol-modified rhBMP-2 by chemical adsorption to obtain DMOG / rhBMP-2@Mg-CHA.

[0009] Preferably, step S1 is specifically as follows: calcium chloride, magnesium chloride and sodium dihydrogen phosphate are dissolved in solutions containing deionized water and ethanol respectively, urea is then dissolved in the sodium dihydrogen phosphate solution as a coprecipitation reagent, and the calcium chloride and magnesium chloride solutions are then added dropwise to the sodium dihydrogen phosphate solution, stirred, and the suspension is transferred to a stainless steel autoclave, heated to 100-180° C. for a period of time, and then naturally cooled; the obtained suspension is filtered, washed with ethanol and water respectively, and freeze-dried.

[0010] Preferably, the specific process of loading DMOG with Mg-CHA in step S2 is: fully dissolving DMOG and Mg-CHA in deionized water respectively, followed by stirring to allow the Mg-CHA particles to fully contact and mix with the drug solution, and finally separating the DMOG that is not combined with Mg-CHA by high-speed centrifugation.

[0011] Preferably, the specific process of loading rhBMP-2 on Mg-CHA in step S2 is as follows: first, rhBMP-2 is reacted with p-carboxybenzaldehyde-PEG-SH in a PBS buffer solution to allow p-carboxybenzaldehyde-PEG-SH to undergo a Schiff base modification reaction with the amino group of rhBMP-2, and then the thiol-modified rhBMP-2 is purified by column chromatography and dialysis; the thiol-modified rhBMP-2 active peptide solution is fully contacted with the above-mentioned Mg-CHA particles and stirred to allow the thiol-modified peptide to coordinate with the Mg ions on the surface of Mg-CHA to form rhBMP-2@Mg-CHA.

[0012] The 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 prepared by the above method still falls within the protection scope of the present invention.

[0013] In the present invention, Mg-CHA has the characteristics of good biocompatibility, high specific surface area, large specific pore volume, uniform and adjustable pore structure, easy surface modification, etc., which is conducive to efficient loading and controllable release of various small molecule drugs and proteins; DMOG on Mg-CHA can promote the expression of hypoxia-inducible factor-ɑ (HIF-ɑ), thereby enhancing the expression of VEGF, and DMOG can not only promote angiogenesis, but also repair bone damage to a certain extent; recombinant human bone morphogenetic protein-2 (rhBMP-2) is an FDA-approved growth factor, rhBMP-2 induces the formation of ectopic ossicles through endochondral ossification, which is similar to the development of natural long bones such as femur and tibia, and endochondral ossification can be controlled by adjusting the implantation time and rhBMP-2 dosage.

[0014] As a universal substrate for 3D printing, polycaprolactone (PCL) has the following advantages: good thermoplasticity, easy processing and molding, and a low melting point (60°C). In addition, PCL is relatively cheap, making it an ideal implant material. The FDA has approved many cases of using PCL-based biomaterials in the field of medical devices, such as surgical sutures made of PGA-PCL (DEXONII®) and PCL-based PU for the treatment of osteoarthritis gaskets (ARTELONTM). These characteristics make PCL very suitable as a raw material for 3D printing technology. Therefore, PCL can be used as a 3D printing substrate for the present dual-factor sequential release of bone powder.

[0015] The specific method is: PCL and the dual-factor sequentially released bone powder are mixed evenly in a certain proportion to obtain a mixture with appropriate performance and biocompatibility. Through 3D printing technology, this PCL-dual-factor sequentially released bone powder can be printed into a bone scaffold with the biological and physical advantages of the two materials. In addition, 3D printing technology has unique advantages in microporous accuracy, personalization, pore regulation, spatial structure complexity, mechanical strength, etc. With these advantages, 3D printed bone scaffolds can promote bony fusion.

[0016] The beneficial effects of the present invention are as follows: DMOG is fully contacted with the mesopores on the surface of Mg-CHA by physical adsorption and is modified on Mg-CHA in large quantities; rhBMP-2 is modified by thiol and is bonded to the Mg2 +Metal coordination forms chemical adsorption. Since chemical adsorption is stronger than physical adsorption, it can achieve the sequential release of DMOG and rhBMP, thereby synergistically promoting osteogenesis. It can be used as a 3D printing material in combination with polycaprolactone (PCL) as a base material to achieve a better osteogenesis effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0018] Figure 1 A schematic diagram of the path for achieving bone repair using the material provided by the present invention; Figure 2 The morphology of Mg-CHA prepared in the present invention under scanning electron microscope; Figure 3 The biocompatibility of the modified Mg-CHA prepared by the present invention; Figure 4 It is a cumulative release curve diagram of various indicators in the material of the present invention. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0020] Example 1 (1) Preparation of Mg-CHA: 1.665-3 g of calcium chloride, 0.16-0.32 g of magnesium chloride and 1.08-2 g of sodium dihydrogen phosphate were dissolved in 8-24 mL of a solution containing deionized water and ethanol (the volume ratio of water to ethanol was 1:3), and then 2.7 g of urea was dissolved in a sodium dihydrogen phosphate solution as a coprecipitation reagent. The calcium chloride and magnesium chloride solutions were then added dropwise to the sodium dihydrogen phosphate solution. After vigorous stirring for 10 min, the suspension was transferred to a stainless steel autoclave and heated at 100-180 °C for 24 h, then naturally cooled to room temperature (25 °C). The suspension was filtered and washed three times with ethanol and water, respectively, and freeze-dried. Figure 2 As shown, the porous structure of Mg-CHA.

[0021] (2) Loading of DMOG: DMOG and Mg-CHA were fully dissolved in deionized water, followed by stirring for 6 hours to allow the Mg-CHA particles to fully contact and mix with the drug solution. Finally, DMOG bound to Mg-CHA was separated by high-speed centrifugation. (3) Loading of rhBMP-2: rhBMP-2 was reacted with p-carboxybenzaldehyde-PEG-SH in PBS buffer solution to allow p-carboxybenzaldehyde-PEG-SH to undergo Schiff base modification reaction with the amino group of rhBMP-2. The thiol-modified rhBMP-2 was then purified by column chromatography and dialysis. The thiol-modified rhBMP-2 active peptide solution was fully contacted with the above-mentioned DMOG@Mg-CHA particles and stirred at room temperature for 6 hours to allow the thiol-modified peptide to coordinate with the Mg ions on the surface of Mg-CHA, thereby finally forming DMOG / rhBMP-2@Mg-CHA.

[0022] Comparative Example 1 In the process of preparing the dual-factor scaffold (DMOG-rhBMP-2@Mg-CHA) in Example 1, the un-thiolated rhBMP-2 was modified on Mg-CHA by physical adsorption to explore the effect of the release pattern of DMOG and rhBMP-2 on the release time.

[0023] Test Case 1. Cell Viability Detection L929 mouse fibroblasts were inoculated into different DMOG / rhBMP-2@Mg-CHAMg-CHA extracts and incubated for 1 day. The cell survival ability was detected by XTT. The results are as follows Figure 3 The cell survival rates of the experimental group and the blank control group were comparable, indicating that the barrier membrane had good biocompatibility.

[0024] Cumulative release The release of DMOG and rhBMP-2 in the osteogenic materials prepared in Example 1 and Comparative Example 1 was detected to obtain a cumulative release curve. The specific steps of the cumulative release test are as follows: a certain amount of osteogenic materials in the comparative example and the example are taken, three parallel samples are set up for each, and the release rate of DMOG and BMP-2 active peptides and their release order are determined by ultraviolet spectrophotometry.

[0025] Specifically: a certain mass of osteogenic material was weighed and immersed in a centrifuge tube containing 10 mL of PBS buffer (pH=7.4), and then placed in a sterile constant temperature incubator at 37°C. 3 mL of PBS was aspirated out at regular intervals and 3 mL of fresh PBS was added. The absorbance of FITC-labeled BMP-2 active peptide was observed at 490 nm, and the absorbance of cy3-labeled DMOG was observed at 552 nm. The absorbance value of the sustained-release solution collected at each time point at the characteristic absorption wavelength was detected, and the drug release amount was calculated according to the standard curve. The cumulative release curve was drawn to calculate the release rate.

[0026] The test results show that DMOG and rhBMP-2 have peak releases in the first and second releases within 39 days, with DMOG releasing most of its release within 1-5 days and being almost completely released within 12 days, while rhBMP-2 releases 50% in about 7 days and then gradually releases slowly, and is still in the slow release process until the 39th day.

[0027] The osteogenic materials released 35% DMOG and 20% rhBMP-2 on the first day of the experiment, 62% DMOG and 40% rhBMP-2 on the fifth day, and 86% DMOG and 57% rhBMP-2 on the 12th day. The test results show that DMOG, which promotes angiogenesis, is released in large quantities during the angiogenesis period, and its release cycle is extended to the main osteogenesis period. The release trend of rhBMP-2 tends to be stable after 12 hours, achieving sustained release, and its sustained release process runs through the main osteogenesis period.

[0028] Load Compared with Comparative Example 1, since both DMOG and rhBMP-2 modify Mg-CHA by physical adsorption, the loading amount of the two is significantly reduced, that is, the loading amount and final release amount of the two on the unit volume of osteogenic material are significantly reduced, resulting in the release concentration of DMOG and rhBMP-2 per unit volume of osteogenic material during the release process not meeting the effective release concentration.

[0029] In summary, the mesoporous Mg-CHA loaded with DMOG and rhBMP-2 prepared by the present invention uses PCL as a substrate to meet the patient's needs for different morphologies of bone scaffolds. 3D printing PCL-double-factor sequential release bone scaffolds; since the adsorption of DMOG and Mg-CHA is physical adsorption, it mainly manifests as reversibility and weak chemical reaction Mg-CHA, so DMOG can be released first. Mg-CHA, as a degradable material, gradually releases chemically adsorbed rhBMP-2 during the degradation process, completing the sequential release of DMOG and rhBMP-2 to simulate the characteristics of the sequential release of angiogenic factors and osteogenic factors in the natural bone repair process.

[0030] Therefore, this material achieves the sequential release of DMOG and rhBMP-2, and the release period of the two is consistent with the cycle of bone repair, and has a good prospect of being applied in the field of bone repair in conjunction with 3D printing.

[0031] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2, characterized in that: Mg-CHA is obtained by modifying carbonated hydroxyapatite with magnesium ions, wherein DMOG is adsorbed on the Mg-CHA, and the Mg on the Mg-CHA 2+ Coordinates with thiolated rhBMP-2.

2. The method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 according to claim 1, characterized in that The method steps include: S1. Based on hydroxyapatite HA, HA is modified by replacing phosphate with phosphate and hydroxyl to form porous carbonated hydroxyapatite CHA, and Mg is modified on CHA to form Mg-CHA; S2. Mg-CHA was loaded with DMOG by physical adsorption, and Mg-CHA was loaded with thiol-modified rhBMP-2 by chemical adsorption to obtain DMOG / rhBMP-2@Mg-CHA.

3. The method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 according to claim 2, characterized in that: The DMOG / rhBMP-2@Mg-CHA prepared in step S2 is compounded with polycaprolactone as a 3D printing substrate to obtain a 3D printing bone repair material.

4. The method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 according to claim 2, characterized in that: Step S1 specifically comprises: dissolving calcium chloride, magnesium chloride and sodium dihydrogen phosphate in a solution containing deionized water and ethanol respectively, then dissolving urea in the sodium dihydrogen phosphate solution as a coprecipitation reagent, then dropping the calcium chloride and magnesium chloride solutions into the sodium dihydrogen phosphate solution, stirring, transferring the suspension into a stainless steel autoclave, heating to 100-180° C. for a period of time, and then cooling naturally; The obtained suspension was filtered, washed with ethanol and water, and freeze-dried.

5. The method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 according to claim 2, characterized in that: The specific process of loading DMOG with Mg-CHA in step S2 is as follows: DMOG and Mg-CHA are fully dissolved in deionized water, respectively, followed by stirring to allow the Mg-CHA particles to fully contact and mix with the drug solution, and finally DMOG that is not combined with Mg-CHA is separated by high-speed centrifugation.

6. The method for preparing a 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 according to claim 2, characterized in that: The specific process of loading rhBMP-2 with Mg-CHA in step S2 is as follows: first, rhBMP-2 is reacted with p-carboxybenzaldehyde-PEG-SH in a PBS buffer solution to allow p-carboxybenzaldehyde-PEG-SH to react with the amino group of rhBMP-2 to undergo a Schiff base modification reaction, and then the thiolated rhBMP-2 is purified by column chromatography and dialysis; The thiol-modified rhBMP-2 active peptide solution was fully contacted with the above-mentioned Mg-CHA particles and stirred to allow the thiol-modified peptide to coordinate with the Mg ions on the surface of Mg-CHA to form rhBMP-2@Mg-CHA.

7. A 3D printed Mg-CHA bone repair material loaded with DMOG and rhBMP-2 prepared by the method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Two-factor gradient slow-release bone repair material and preparation method thereof

    CN116139340A